Modelling and experimental study on β-phase depletion behaviour of HVOF sprayed free-standing CoNiCrA1Y coatings during oxidation - Chen, H.; Jackson, G.A.; Voisey, K.T.; McCartney, D.G. (Elsevier, 2016)
This paper investigates the β-phase depletion behaviour during oxidation of free-standing CoNiCrA1Y (Co-31.7%Ni-20.8%Cr-8.1%A1-0.5%Y, all in wt%) bond coats prepared by high velocity oxy-fuel (HVOF) thermal spraying. The microstructure of the coatings was characterised using scanning electron microscopy with energy dispersive X-ray (EDX) analysis and electron backscatter diffraction (EBSD). It comprises a two phase structure of fcc γ-Ni and bcc β-NiA1, with grain sizes varying largely from 0.5 to 2 μm for both phases. Isothermal oxidation tests of the free-standing coatings were carried out at 1100 °C for times up to 250 h. The β phase depletion behaviour at the surface was measured and was also simulated using Thermo-Calc and DICTRA software. An A1 flux function derived from an oxide growth model was employed as the boundary condition in the diffusion model. The diffusion calculations were performed using the TTNi7 thermodynamic database together with the MOB2 mobility database. Reasonable agreement was achieved between the measured and the predicted element concentration and phase fraction profiles after various time periods. Grain boundary diffusion is likely to be important to element diffusion in this HVOF sprayed CoNiCrA1Y coating due to the sub-micron grains.